PENGOBATAN TRADISIONAL PENYAKIT MATA PADA MANUSKRIP-MANUSKRIP YANG TERSIMPAN DI YOGYAKARTA - Sri Harti Widyastuti (JURNAL IKADBUDI, 2013)
The writing is based on four manuscripts that contains fitotherapy of eye disease namely Boekoe Primboen Djampi Djawi, Serat Primbon, Serat Primbon Jawi, and Serat Primbon. The method used is the method of modern philology. The analysis used is descriptive analysis. The validity the data iis measured by using semantic validity, and reliability by using intrarater, the use of secondary data in the form of a dictionary. The results showed, that based on the description of the manuscript, it is possible that the texts in the Serat Primbon examined, is a product of the era of new Java (18th century), in the transliteration was found some words that are no longer popular in the community, in the translation that has been done, there are also words that are difficult to translate because there is no synonym word in the dictionary. In fitotherapy of eye disease there are 48 kinds of herbal ingredients which are grouped into 6 sections. Among the herbal ingredients are herbal ingredients which is difficult to find its equivalent in everyday life as well as in the dictionary, so it is possible these herbal ingredients had not recognized by modern society today. Key words: fitotherapy, manuscripts, eye disease